2D Materials: Controlled Micro/Nanodome Formation in Proton‐Irradiated Bulk Transition‐Metal Dichalcogenides (Adv. Mater. 44/2019). Issue 44 (1st November 2019) - Tedeschi, Davide; Blundo, Elena; Felici, Marco; Pettinari, Giorgio; Liu, Boqing; Yildrim, Tanju; Petroni, Elisa; Zhang, Chris; Zhu, Yi; Sennato, Simona; Lu, Yuerui; Polimeni, Antonio
Abstract : Proton irradiation of bulk transition‐metal dichalcogenides leads to the blistering of atomically thin domes filled with hydrogen, as described by Yuerui Lu, Antonio Polimeni, and co‐workers in article number 1903795 . The domes stud the crystal surface and locally turn the dark bulk material into an efficient light emitter. They can be produced with ordered positions and sizes tunable from the nanometer to the micrometer scale, with important prospects for so far unattainable applications.